Respuesta :
Answer:
[tex]\huge\boxed{x = 6 , y = -2}[/tex]
Step-by-step explanation:
[tex]\sf \frac{1}{2} x - 3y = 9-----------(1)\\5x + y = 28 ----------(2)[/tex]
Taking equation (1)
[tex]\sf \frac{1}{2} x -3 y=9[/tex]
Multiplying both sides by 2
[tex]\sf x-6y = 18[/tex]
Adding 6y to both sides
[tex]\sf x = 18+6y[/tex]
Putting this in (2)
5(18+6y) + y = 28
5(18+6y) + y = 28
90 + 30y+y = 28
31y+90-28 = 0
31 y + 62 = 0
31y = -62
Dividing both sides by 31
y = -2
Now,
x = 18 + 6y
x = 18+6(-2)
x = 18-12
x = 6
1/2x - 3y = 9 (1)
5x + y = 28 (2)
(1) x 2
x - 6y = 18
(2) x 6
30x + 6y = 168
—————
x - 6y = 18 (3)
30x + 6y = 168 (4)
(3) + (4)
31x = 186
x = 6
sub x into (2)
30 + y = 28
y = -2
—————
x = 6
y = -2
5x + y = 28 (2)
(1) x 2
x - 6y = 18
(2) x 6
30x + 6y = 168
—————
x - 6y = 18 (3)
30x + 6y = 168 (4)
(3) + (4)
31x = 186
x = 6
sub x into (2)
30 + y = 28
y = -2
—————
x = 6
y = -2